Pengaruh Financial Capital, dan Literasi Keuangan terhadap Kinerja Usaha Kecil dan Menengah (UKM) di Kota Malang - Marija Marija; Sihwahjoeni Sihwahjoeni; Gaguk Apriyanto (Jurnal Akuntansi dan Perpajakan, 2021)
Small and Medium Enterprises (SME) are businesses that are very helpful in improving the economy of the community. SMEs need special attention to maintain their existence in the business world. However, various problems are still faced by SMEs in Malang, these problems are related to capital, bookkeeping, standardization, marketing and sales. The purpose of this study was to analyze the effect of financial capital and financial literacy on the performance of small and medium enterprises (SME) in Malang. The research design used causality research with a survey method. The population as the sample is the owner of SME registered in the Cooperative and SME Office of Malang City. Respondents in this study were 91 SME owners engaged in manufacturing. Primary data used comes from distributing questionnaires that are given directly. The data analysis technique used multiple linear regression. The results showed that financial capital and financial literacy had a positive and significant effect on the performance of small and medium enterprises (SME) in Malang.